The Influence of Motivation, Work Environment and Work Discipline on Employee Performance at PT. Tamim Zada Rajawali - Nurrachma, Farhana Najmi; Krisnandi, Herry; Digdowiseiso, Kumba (International Journal of Social Service and Research, 2024)
This research aims to investigate the specific dimensions of motivation, work environment, and work discipline and their influence on employee performance at PT. Tamim Zada Rajawali. Utilizing quantitative techniques and descriptive methods, the study employs multiple linear regression inferential analysis to interpret the data. Primary data is collected through closed questionnaires distributed to 100 respondents, and the analysis is conducted using the Statistical Product and Service Solution (SPSS) program version 23.0. The findings reveal a notable contradiction in the impact of motivation (X1), which exhibits a negative and significant effect, contrary to initial expectations. On the other hand, Work Environment (X2) and Work Discipline (X3) demonstrate positive and significant effects on the dependent variable, namely employee performance. The unexpected result regarding motivation prompts the need for further investigation and clarification. Based on the study results, it is recommended that companies pay close attention to and evaluate employee performance to enhance overall effectiveness. This research contributes valuable insights for organizations aiming to improve employee performance through a comprehensive understanding of motivation, work environment, and work discipline dynamics.